Implementasi Algoritma Ternary Comma Code (TCC) Dalam Mengkompresi File Audio Pada Aplikasi Perekam Suara - Ayu Nita Irwanda (Bulletin of Multi-Disciplinary Science and Applied Technology, 2022)
Techniques in compressing audio files are commonly used for transmission and storage processes, namely to reduce bottlenecks in the input or output process, save data storage space and facilitate the distribution of data and files with electronic media and removable media. A voice recorder is an electronic device that picks up sound or frequency waves and is designed to fit an application that can be saved in digital or other network formats. This voice recorder application is widely used in the modern era today is also very helpful in our daily life, for example writing applications, games, video and voice, but must be adjusted as needed. Based on the implementation of the algorithm used is the Ternary Comma Code (TCC). This method is a binary number (line2) which is based on 2 bit numbers 0 and 1.In the use of the TCC algorithm method, it allows audio file data in voice recording applications to reduce the redundancy of files to save or send in an efficient form and so we can compress these important files to save more memory space, because a storage system requires a large enough space. The use of the data size is getting bigger and bigger so the process can change it by compressing the original data.